Nutritional status of children and adolescents based on body mass index: agreement between World Health Organization and International Obesity Task Force - Timothy Gustavo Cavazzotto; Marcos Roberto Brasil; Vinicius Machado Oliveira; Schelyne Ribas da Silva; Enio Ricardo V. Ronque; Marcos Roberto Queiroga; Helio Serassuelo Junior (Sociedade de Pediatria de São Paulo, 2014)
Objective: To investigate the agreement between two international criteria for classification of children and adolescents nutritional status. Methods: The study included 778 girls and 863 boys aged from six to 13 years old. Body mass and height were measured and used to calculate the body mass index. Nutritional status was classified according to the cut-off points defined by the World Health Organization and the International Obesity Task Force. The agreement was evaluated using Kappa statistic and weighted Kappa. Results: In order to classify the nutritional status, the agreement between the criteria was higher for the boys (Kappa 0.77) compared to girls (Kappa 0.61). The weighted Kappa was also higher for boys (0.85) in comparison to girls (0.77). Kappa index varied according to age. When the nutritional status was classified in only two categories - appropriate (thinness + accentuated thinness + eutrophy) and overweight (overweight + obesity + severe obesity) -, the Kappa index presented higher values than those related to the classification in six categories. Conclusions : A substantial agreement was observed between the criteria, being higher in males and varying according to the age.